KEMANDIRIAN ANAK BERKEBUTUHAN KHUSUS (ABK) MELALUI METODE KEPRAMUKAAN (STUDI KASUS DI SLB NEGERI PUNUNG) - Aprilia, Reza; Tisngati, Urip; Erviana, Lina (PGSD STKIP PGRI Pacitan, 2025)
This research aims to determine the independence of Children with Special Needs (ABK) through scouting methods at SLB Negeri Punung. The research was descriptive qualitative with a single case study approach. The informants consisted of 2 teachers as scout leaders and 5 students, chosen to use purposive sampling. Data collection methods consist of observation, interviews and documentation. Qualitative data analysis was chosen to use the Miles concept and Huberman through three activities, namely data reduction, data display, and conclusion drawing/ verification. The results obtained in this study are: 1) scouting activities at SLB Negeri Punung are superior extracurricular activities by implementing scouting methods including the scout code of honor, learning by doing, and partnerships with adult members, 2) scouting activities have implications for student independence, the observed indicators include initiative, self-confidence, decision-making ability and progressiveness, 3) obstacles in this activity are the difficulty in understanding the material presented by the teacher, so it requires support from parents and teachers to increase student participation. Keywords: Independence, Children with Special Needs, Scouting Methods